A Case of Hereditary Leiomyomatosis and Renal Cell Carcinoma. (7th April 2016) - Mehrtens, Sarah; Veitch, David; Kulakov, Elizabeth; Perrett, Conal M.
Abstract : A 49-year-old lady presented with multiple recurring painful lesions over her thighs, arms, and back. Past medical history included a left sided nephrectomy for renal cell carcinoma and a hysterectomy for multiple uterine fibroids (leiomyomas). Histopathological examination revealed changes consistent with pilar leiomyomas. Gene mutation analysis confirmed a diagnosis of hereditary leiomyomatosis and renal cell carcinoma. Hereditary leiomyomatosis and renal cell carcinoma is an uncommon autosomal dominant condition characterised by the concurrent presentation of cutaneous and uterine leiomyomas. Renal cell carcinoma associated with this condition is more aggressive and a significant cause of mortality. Due to this association with potentially fatal renal cell carcinoma we felt that it was important to highlight this case with an update on pathophysiology and management.